Digital Dependency and Political Economy in Developing Countries: A Theoretical and Empirical Analysis - Islam, MD. Rafiul; Jerin, Afia Jahin (Penerbit Hellow Pustaka, 2025)
This paper investigates the intersection of political economy and digital dependency in developing country, highlighting how reliance on external digital infrastructure platforms and artificial intelligence (AI) ecosystem and shape sovereignty, development and inequality. Drawing on secondary data from World Bank, IMF, UNCTAD, ILO, and peer-reviewed literature, the study applied dependency theory and digital colonialism framework to evaluate challenges and opportunities in digital economy. findings included that while digital technology foster growth and innovation they also deepen vulnerabilities to external shocks and reinforce structural inequalities. policy recommendation emphasize strengthening domestic digital infrastructure, ensure data sovereignty, and fostering inclusive AI adoption.